Nerve Repair With Fibrin Nerve Conduit and Modified Suture Placement. Issue 10 (23rd October 2018) - Wang, Wenjin; Degrugillier, Lucas; Tremp, Mathias; Prautsch, Katharina; Sottaz, Lima; Schaefer, Dirk J.; Madduri, Srinivas; Kalbermatten, Daniel
ABSTRACT: Sutureless nerve repair has been regarded as a promising technique for nerve repair as the suture materials often results in neuroma formation and scar tissue that impede nerve regeneration. The aim of this study was to analyze the mechanical stability and morphological outcome of sutureless repair using fibrin glue conduit and an alternative approach of modified suture placement. Using rat sciatic nerve, we tested the following experimental conditions: conventional suture repair; single suture combined with fibrin glue repair, and fibrin conduit reinforced with modified suture or fibrin glue. Nerve detachment anatomical measures such as axon density, myelin, and fiber caliber were analyzed for evaluation of nerve regeneration. Muscle atrophy were evaluated by muscle wet weight and H&E staining. All animals in sutureless repair group exhibited complete detachment or elongation by two or four weeks after repair. No detachment was found in any other groups. Animals treated with fibrin conduit reinforced with modified suture showed better axonal regeneration with good alignment. There were no significant differences in axon caliber among the groups. Muscle atrophy was found in all groups and there was no significant difference in muscle wet‐weight among the groups. In summary, sutureless nerve repair with fibrin glue was mechanically unstable for resistance of mechanical stretches, fibrin glue conduit with modified suture placement is mechanically stable and resulted in better morphological outcome. Anat Rec, 301:1690–1696, 2018. © 2018 Wiley Periodicals, Inc.